STRATEGI PERSONAL BRANDING “LEDIA HANIFA”: KUNCI SUKSES TERPILIH EMPAT PERIODE SEBAGAI POLITISI WANITA DI DPR-RI - Dirgantara, Khantia Ridwan; Sjoraida, Diah Fatma; Sjafirah, Nuryah Asri; Setianti, Yanti (Mediakom : Jurnal Ilmu Komunikasi, 2024)
Personal branding has become a key element in winning political contests, particularly for female politicians who face challenges related to stereotypes and intense competition. This study analyzes the personal branding strategies of Ledia Hanifa, a female politician who has been elected four consecutive times as a member of the Indonesian House of Representatives (DPR-RI) since 2009. Employing a case study method with a qualitative approach, this research utilizes in-depth interviews and literature studies to explore the dimensions of personal branding based on the Brand Identity Prism theory popularized by Jean-Noel Kapferer. The findings reveal that Ledia Hanifa's personal branding encompasses a physical appearance that reflects religiosity, a friendly and humorous personality, Islamic cultural values, collaborative relationships, and a self-image that is perceived as trustworthy and caring. The personal branding strategies implemented leverage both online and offline media to build relationships with the public and reinforce positive perceptions. This study underscores the importance of consistency and technological adaptation in establishing personal branding for female politicians to enhance public attention.